Forms of expression and recovery of vigor in mature trees of Lagerstroemia indica L - Ivasko Júnior, Severo; Lombardi, Kátia Cylene; Bobrowski, Rogério (Scientia Plena, 2019)
The present study aimed to characterize different forms of vigor expression and its recovery in mature trees of Lagerstroemia indica L. planted in public spaces of Irati, Brazil. After measuring the vegetative vigor (shoot growth, internode length, leaf area and leaf color), physiological vigor (chlorophyll a and b content) and flowering vigor (inflorescence width and length) in the growing season of 2016, we applied lime and fertilizers in different treatments in the portion of soil under the dripline of each tree. These treatments consisted of an increase of 100% nitrogen, phosphorus and potassium contents measured in the soil, based on previous soil analysis. In order to evaluate the effect of fertilization, in the growing season of 2017 we remeasured the vigor of trees. We observed that treatments with potassium and phosphate fertilization provided the highest mean values for shoot growth, the mean distance of internodes, leaf area, inflorescence width and length. The variables dark green color index and content of chlorophyll a and b were not influenced by fertilizer treatments. Our findings show that fertilizers increased the expression of all variables related to vegetative vigor of L. indica in the urban environment, except for the dark green color index. This suggests .that nutrient availability is generally a limiting factor for the urban tree’s growth. The shoot length can be used to characterize the vegetative vigor, and the inflorescence length in the evaluation of the flowering vigor.